Can visible signs predict concussion diagnosis in the National Hockey League?. Issue 17 (4th April 2017) - Echemendia, Ruben J; Bruce, Jared M; Meeuwisse, Willem; Hutchison, Michael G; Comper, Paul; Aubry, Mark
Abstract : Background: Early identification and evaluation of concussions is critical. We examined the utility of using visible signs (VS) of concussion in predicting subsequent diagnosis of concussion in NHL players. Methods: VS of concussion were identified through video review. Coders were trained to detect and record specific visual signs while viewing videos of NHL regular season games. 2460 games were reviewed by at least two independent coders across two seasons. The reliability, sensitivity and specificity of these VS were examined. Results: VS were reliably coded with inter-rater agreement rates ranging from 73% to 98.9%. 1215 VS were identified in 861 events that occurred in 735 games. 47% of diagnosed concussions were associated with a VS but 53% of diagnosed concussions had no VS. Of the VS, only loss of consciousness, motor incoordination, and blank/vacant look had positive likelihood ratios greater than 1, indicating a positive association with concussion diagnoses. Slow to get up and clutching of the head were observed frequently but had low positive predictive values. Sensitivity decreased and specificity increased when multiple VS occurred together. Conclusions: Non-medical personnel can be trained to reliably identify events in which VS occur and to reliably identify specific VS within each of those events. VS can be useful to detect concussion early but they are not enough since more than half of physician diagnosed concussions occurred without the presence of a visual sign. The results underscore the complexity of this injury and highlight the need for comprehensive approaches to injury detection.